2010
DOI: 10.1021/np100426j
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Structures of 1,5-Dihydroxy-3,8-epoxyvalechlorine, Volvaltrate B, and Valeriotetrate C from Valeriana jatamansi and V. officinalis

Abstract: The structures of 1,5-dihydroxy-3,8-epoxyvalechlorine (1a) and volvaltrate B (6a), two new chlorinated iridoids isolated from Valeriana jatamansi and V. officinalis, respectively, were originally assigned on the basis of spectroscopic methods. Reinvestigation using X-ray analysis and chemical transformation revealed that the original assignment of H-7 in 1a and OH-8 in 6a should be inverted and that the structures should be revised to 1 and 6, respectively. Correspondingly, the structure of valeriotetrate C (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Therefore, the planar structure of 1 was established. The stereochemistry including the absolute configuration of valepotriates has been well elucidated by NOE experiments, chemical transformation, and X-ray analysis in the previous reports [7,14]. The singlet of H-1 and H-9 in 1 suggested that the dihedral angle of these two protons is close to 908.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Therefore, the planar structure of 1 was established. The stereochemistry including the absolute configuration of valepotriates has been well elucidated by NOE experiments, chemical transformation, and X-ray analysis in the previous reports [7,14]. The singlet of H-1 and H-9 in 1 suggested that the dihedral angle of these two protons is close to 908.…”
Section: Resultsmentioning
confidence: 80%
“…These observations, coupled with biogenetic grounds, suggested that 2 has the same configuration of iridoid nucleus as 1. The R configuration of the a-(isovaleroxy)isovaleroxy moiety was established by basic hydrolysis of 2, which yielded R-a-(isovaleroxy)isovaleric acid on the basis of its optical rotation data {½a 20 D þ 8.2 (c ¼ 0.10, CHCl 3 )} [7]. Therefore, 2 was defined as valtral B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative configuration of 1 was further established by ROESY experiment ( Figure 2 and Supplementary Figures S8, S9 ) and comparison the spectroscopic data with those reported valepotriates (Demirezer et al, 1999; Tang et al, 2002; Wang et al, 2008, 2014; Lin et al, 2010b, 2013). Generally, naturally occurring iridoids display α-orientation for H-1 and β-orientation for H-9.…”
Section: Resultsmentioning
confidence: 88%
“…Valtrate, acevaltrate were important sedative-hypnotics chemical bulk drugs. Iridoid esters could also inhibit the growth and proliferation of human tumor cell lines (Lin et al, 2009;Lin et al, 2010), with the mechanism unknown. In addition, valtrate and its analogs are Rev-export inhibitors demonstrated other effects such as anti-HIV (Watanabe et al, 2011), and reversed tumor RESEARCH ARTICLE (Turner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%